Relationship between cervical dilation and time to delivery in women with preterm labor - Mariarosaria Di Tommaso; Viola Seravalli; Francesca Vellucci; Mauro Cozzolino; Marina Spitaleri; Tommaso Susini (Journal of Research in Medical Sciences, 2015)
Background: Early recognition of the signs and symptoms of preterm labor (PTL) is important in order to establish treatment. Our aim was to determine the relation between cervical dilatation and time interval from admission to delivery in women with preterm labor. Materials and Methods: A retrospective cohort study was conducted on 83 singleton gestations admitted for preterm labor between 24 weeks and 34 weeks, who subsequently delivered preterm. Women were categorized into three groups of cervical dilatation (0-2 cm, 3-6 cm, >6 cm) and the time interval from admission to delivery was compared. Cox regression analysis was performed to assess the association between cervical dilatation and time interval from admission to delivery. The other variables examined were gestational age (GA) at admission and length of the cervix, when performed. Results: The time interval from admission to delivery was significantly shorter in women with higher dilatation of the cervix (p < 0.02) and in those admitted at a more advanced gestational age (p < 0.05). Forty-eight percent of women with cervical dilatation 0-2 cm delivered in the first 48 h compared to 85% of the women with a dilatation of 3-6 cm. No significant association was found between the length of the cervix and the time interval to delivery. Conclusion: Dilatation of the cervix and gestational age at admission are associated with the time interval to delivery in women with preterm labor. The assessment of the length of the cervix is unlikely to add clinical information in women with an already dilated cervix.